Analisis Seismisitas Di Sulawesi Utara Berdasarkan Data Gempa Bumi Tahun 2018-2022 - Rut Seriaty; Armstrong Sompotan; Cyrke A. N. Bujung (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The objective of this study is to assess the seismic activity and brittleness of rocks, as well as the level of risk associated with natural disasters in North Sulawesi. The earthquake data utilized is derived from secondary sources spanning the years 2018 to 2022, specifically received from the Manado Geophysical Station. The data processing encompasses many criteria such as locations, magnitude, depth, and time of occurrence. The Guttenberg-Richter approach yields a seismicity level ranging from 4.121 to 5.589, while the rock fragility falls within the range of 0.98 to 1.072. The Talaud Islands Regency has the highest level of seismicity, measured at 5,589, while the East Bolaang Mongondow Regency has the lowest level, measured at 4,121. The Talaud Islands Regency region has the highest degree of rock fragility, measured at a value of 1.072, while the North Bolaang Mongondow Regency area demonstrates the lowest amount of rock fragility, measured at a value of 0.98. The Talaud Islands have the most significant earthquake risk, whereas the areas with the least danger include Minahasa, Sangihe Islands, Siau Tagulandang Biaro, Manado, Bitung, Tomohon, Kotamobagu, Southeast Minahasa, South Minahasa, and North Minahasa.